Modulation of Human Leukocyte Antigen-C by Human Cytomegalovirus Stimulates KIR2DS1 Recognition by Natural Killer Cells - van der Ploeg, Kattria; Chang, Chiwen; Ivarsson, Martin A.; Moffett, Ashley; Wills, Mark R.; Trowsdale, John (Frontiers in Immunology, 2017)
The interaction of inhibitory KIRs with HLA class I molecules has been characterized in detail. In contrast, activating members of the KIR family, although closely related to inhibitory KIRs, appear to interact weakly, if at all, with HLA class I. KIR2DS1 is the best studied activating KIR and it interacts with C2 group HLA-C (C2+HLA-C) in some assays, but not as strongly as KIR2DL1. We used a mouse 2B4 cell reporter system, which carries NFAT-GFP with KIR2DS1 and a modified DAP12 adaptor protein. KIR2DS1 reporter cells were not activated upon co-culture with 721.221 cells transfected with different HLA-C molecules, or with IFN-γ stimulated primary dermal fibroblasts. However, KIR2DS1 reporter cells and KIR2DS1+ primary NK cells were activated by C2+HLA-C homozygous Human Fetal Foreskin Fibroblasts (HFFFs) but only after infection with specific clones of a clinical strain of HCMV. Active viral gene expression was required for activation of both cell types. Primary NKG2A-KIR2DS1+ NK cell subsets degranulated after co-culture with HCMV infected HFFFs. The W6/32 antibody to HLA class I blocked the KIR2DS1 reporter cell interaction with its ligand on HCMV infected HFFFs but did not block interaction with KIR2DL1. This implies a differential recognition of HLA-C by KIR2DL1 and KIR2DS1. The data suggest that modulation of HLA-C by HCMV is required for a potent KIR2DS1-mediated NK cell activation.